Perceived and Ideal Body Image in Young Women in South Western Saudi Arabia - Atika Khalaf; Albert Westergren; Vanja Berggren; Örjan Ekblom; Hazzaa M. Al-Hazzaa (Hindawi Limited, 2015)
Objectives. The aim of this study was to investigate perceived and ideal body image (BI) and associated factors among female university students in Saudi Arabia. Methods. This cross-sectional study included 663 university female students. Anthropometric measurements including weight, height, BMI, and BI perception (the 9-figure silhouette) were obtained. Descriptive and logistic regression analysis were conducted. Results. An agreement between actual, perceived, and ideal BI was found in 23% of the participants. Behavioral (activity levels), social (presence of obese parents and fathers' level of education), and economic factors (households' monthly income, number of cars in the household, and kind of residence) were positively and significantly associated with the desire to be thinner. Similarly, socioeconomic associations (number of sisters and number of cars in the household) correlated positively and significantly with the desire to be heavier. Conclusions. The whole family should rather be considered in interventions related to appearance concerns and BI discrepancies. Furthermore, campaigns targeting improvement of adolescents' physical self-image should be a major priority of the public health sector.